The Effect of Teaching Kitab of Hadith al-Arba’in al-Nawawiyah on Improving the Character of MAPK Makassar Students - Abdul Rahman Sakka; Safaruddin; Hikmawati Sultani; Abdul Salam (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This quantitative study explores the novel effect of teaching al-Arba'in al-Nawawiyah on character development among MAPK students in Makassar. By employing linear regression analysis on a sample of 92 students, we show that student motivation is the primary predictor of character development, explaining 23% of the variance. The data were collected through a questionnaire. While teaching methods and teacher qualifications were not significant predictors, the findings offer new insights into motivation-driven character formation in Islamic education. This study contributes to the growing body of literature by providing empirical evidence for the role of intrinsic motivation in enhancing moral and social behaviors among secondary school students, particularly in the context of hadith-based learning. Although the regression model used explained 23% of the variation in student character, student motivation was proven to be the main factor in better character formation